Pandangan Dunia Tragis Generasi Revolusioner Dalam Novel Jawaizu Lil Abthal Karya A?mad ‘Auni: Strukturalisme Genetik - Muhamad Rian Nuryana; Yani Heryani; Khomisah Khomisah (Jurnal Impresi Indonesia, 2026)
This study examines the tragic worldview (vision tragique du monde) of the revolutionary generation as represented in Ahmad ‘Auni’s novel Jawaizu Lil Abthal (2019). Two research questions are addressed: first, how the tragic worldview is represented within the novel's narrative structure; and second, how structural homology exists between that tragic worldview and the sociopolitical conditions of Egyptian society following the January 25, 2011 Revolution. This study employs a sociology of literature approach through Lucien Goldmann's genetic structuralism framework with a qualitative-descriptive method and dialectical analysis technique. The analytical focus is confined to the tragic worldview dimension, comprising four characteristics: inauthenticity, mediocritas, fragmentation, and degradation. Data were collected through library research, with the novel as the primary data source. The findings reveal that all four characteristics are systematically manifested through 34 data points across the novel's narrative elements. The identified structural homology demonstrates that Rami’s inauthenticity corresponds to the ideological disorientation of Egyptian youth who participated in the revolution without mature commitment; mediocritas corresponds to the failure of substantive change in the post-Mubarak era; fragmentation corresponds to the disintegration of the opposition movement into mutually conflicting factions; and degradation corresponds to the restoration of authoritarianism that systematically punished activists and betrayed revolutionary values.